FIBER DISPERSION MEASUREMENTS USING MACH-ZEHNDER INTERFEROMETER - Le Canh Trung (Tạp chí Khoa học)
We present an efficient technique for measuring chromatic dispersion using a modified Mach-Zehnder interferometer in conjunction with with a supercontinuum light source. Newport's femto White photonic crystal fiber and the Polish ITME Institute's NL40F fiber were used for chromatic dispersion and to verify our experimental system's accuracy.